LYCAT, a homologue of C. elegans acl-8,acl-9, and acl-10, determines the fatty acid composition of phosphatidylinositol in mice - Rieko Imae (Journal of Lipid Research, 2012)
Mammalian phosphatidylinositol (PI) has a unique fatty acid composition in that 1-stearoyl-2-arachidonoyl species is predominant. This fatty acid composition is formed through fatty acid remodeling by sequential deacylation and reacylation. We recently identified three Caenorhabditis elegans acyltransferases (ACL-8, ACL-9, and ACL-10) that incorporate stearic acid into the sn-1 position of PI. Mammalian LYCAT, which is the closest homolog of ACL-8, ACL-9, and ACL-10, was originally identified as a lysocardiolipin acyltransferase by an in vitro assay and was subsequently reported to possess acyltransferase activity toward various anionic lysophospholipids. However, the in vivo role of mammalian LYCAT in phospholipid fatty acid metabolism has not been well elucidated. In this study, we generated LYCAT-deficient mice and demonstrated that LYCAT determined the fatty acid composition of PI in vivo. LYCAT-deficient mice were outwardly healthy and fertile. In the mice, stearoyl-CoA acyltransferase activity toward the sn-1 position of PI was reduced, and the fatty acid composition of PI, but not those of other major phospholipids, was altered. Furthermore, expression of mouse LYCAT rescued the phenotype of C. elegans acl-8 acl-9 acl-10 triple mutants. Our data indicate that LYCAT is a determinant of PI molecular species and its function is conserved in C. elegans and mammals.